Water conflicts in Africa - Song, Chun (Harvard University, 2025)
Purpose: This dataset includes detailed information on intra-state water conflicts across African countries (2010–2024). Nature: This dataset extends the raw datasets downloaded from Armed Conflict Location & Event Data Project (ACLED) data by further identifying water-related conflicts, then categorizing them into resource-based water disputes, water infrastructure attacks, and protests related to water cuts or water shortages. Scope: 14 years for African countries.